Oncoplastic breast conserving surgery and oncological outcome: Systematic review. Issue 5 (May 2016) - Yiannakopoulou, E.C.; Mathelin, C.
Abstract: Oncoplastic surgery consists a new approach for extending breast conserving surgery possibilities This manuscript aimed to systematically review data on the oncological outcome of oncoplastic breast surgery. Electronic databases were searched with the appropriate search term up to and included April 2013. Inclusion criteria: full publications including at least 10 patients and providing evidence on at least one of the following outcomes: margin involvement, local recurrence, metastatic disease, death number. Forty studies including 2830 patients, met inclusion criteria; twenty one studies investigated volume displacement techniques; fifteen studies investigated volume replacement techniques; four studies presented data on various oncoplastic techniques. Study quality was low. The majority of studies were observational studies. The length of follow up was relatively short, with only two studies reporting a median duration longer than 60 months. Only seven studies including more than 100 patients. There was great variation in the frequency of margin involvement ranging between 0% and 36% of patients. Local recurrence was observed in 0–10.8% of patients. Distant metastasis was observed in 0–18.9% of patients. In conclusion, long term oncological outcome of oncoplastic surgery for breast cancer is not adequately investigated. Further research efforts should focus on Level I evidence on oncological outcome of oncoplastic surgery.